2012
DOI: 10.3732/ajb.1100532
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellite primers for Jatropha curcas (Euphorbiaceae) and transferability to congeners

Abstract: The primers developed here revealed polymorphic loci that are suitable for genetic diversity and structure, mating system, and gene flow studies in J. curcas, and some congeners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 8 publications
2
11
0
1
Order By: Relevance
“…A similarly low number of alleles was also documented by Sharma and Chauhan (2011), who found 2-6 alleles by transferring the SSR castor primer to jatropha. Similarly, Na-Ek et al (2011) observed 2-4 alleles per locus, and Bressan et al (2012) found 2-8 alleles per locus from new SSR markers developed for jatropha.…”
Section: Discussionmentioning
confidence: 91%
“…A similarly low number of alleles was also documented by Sharma and Chauhan (2011), who found 2-6 alleles by transferring the SSR castor primer to jatropha. Similarly, Na-Ek et al (2011) observed 2-4 alleles per locus, and Bressan et al (2012) found 2-8 alleles per locus from new SSR markers developed for jatropha.…”
Section: Discussionmentioning
confidence: 91%
“…By analyzing Table 2, we see that studies performed to test the transferability between species of the same genus generally presented the highest rates. Bressan et al, (2012) observed a 67% transferability rate when they tested 9 pairs of primers designed for Jatropha curcas in Jatropha podagrica, Jatropha pohliana and Jatropha gossypifolia. Similarly, Sousa et al, (2009) obtained an average of 73% transferability from Centrosema pubercens primers in eleven species of the genus Centrosema.…”
Section: Resultsmentioning
confidence: 99%
“…Five of these loci clearly displayed distinct banding patterns between 26 Mexican accessions (nontoxic) and the 10 Asian accessions (toxic). In the studies of Bressan et al [59], nine polymorphic microsatellite loci with 2-8 alleles per locus were identified, of which six loci showed transferability to three congeners: Jatropha podagrica, Jatropha pohliana and Jatropha gossypiifolia. Based on the whole genome sequences, Sato et al [77] identified about 41 000 SSR loci in the 289 Mb sequences of the J. curcas genome.…”
Section: Ssr Markersmentioning
confidence: 99%